Alkaline lysis-recombinase polymerase amplification combined with CRISPR/Cas12a assay for the ultrafast visual identification of pork in meat products. (30th July 2022) - Zhao, Gang; Wang, Jin; Yao, Chanyu; Xie, Peichun; Li, Xiangmei; Xu, Zhenlin; Xian, Yanping; Lei, Hongtao; Shen, Xing
Highlights: An RPA-CRISPR/Cas12a method for rapid detection of pork has been established. As low as 10 -3  ng of pig genomic DNA can be detected within 30 min by a portable box. The LOD can reach to 0.1% (w/w), and it is suitable for on-site rapid detection. Verified by 125 meat products, this method can be used for accurate assay of samples. Abstract: The "Horsemeat Scandal" makes people pay more attention to the meat authenticity. However, expensive equipment, complicated operations, and professional personnel of current methods limit their field testing. In this study, CRISPR/Cas12a combined with recombinase polymerase amplification was used to establish a sensitive and rapid detection method for pig-derived component. The detection limit can reach to 10 -3  ng for pig DNA and be completed within 30 min. Beef and pork binary mixture models under different processing conditions of raw meat, boiled, and high-pressure were tested. Combining with two different DNA extraction methods, the detection limits of pork are as low as 0.1% and 0.001% (w/w), respectively. After 125 commercial products are tested, the results are completely consistent with the Chinese national standard real-time PCR method. This method not only has better detectability, but also can quickly and conveniently realize the visual identification of pig-derived ingredients, thus is suitable for on-site detection.